Advancing equity in cross-cultural psychology: embracing diverse epistemologies and fostering collaborative practices - Anjum, Gulnaz; Aziz, Mudassar (Frontiers in Psychology, 2024)
Psychology, and cross-cultural psychology (CCP) in particular, plays a pivotal role in understanding the intricate relationship between culture and human behavior. This paper sheds light on the challenges of inequity and marginalization, especially concerning scholarship from the Global South, which have roots in historical colonial practices. It highlights how intellectual extractivism and the predominance of Western research methodologies often overlook the contributions of Global South scholars and indigenous ways of knowing. Such imbalances risk narrowing the scope of psychological inquiry, privileging American and European perspectives, and undermining the richness of global human experiences. This paper calls for a shift towards more equitable collaborations and the recognition of diverse epistemologies. By advocating for genuine representation in research and valuing local knowledge, it proposes pathways for a more inclusive and authentic exploration of human behavior across cultures.